The Role of E-Satisfaction in Influencing Online Repurchase Intention on Marketplace Sites in Indonesia - Chaniago, Bunga; Alfansi, Lizar; Ekaputri, Seprianti; Hardi, Effed Darta (Jurnal Economia, 2024)
AbstractThis study aims to see whether the e-satisfaction variable can have a mediating effect on e-service quality and perceived ease of use on online repurchase intention on marketplace sites. The consumers on the marketplace website were provided with online questionnaires as part of the research method. A total of 268 respondents were gathered. The data were then analyzed utilizing LISREL 8.70 software. The results revealed that e-satisfaction could partially mediate between e-service quality and online repurchase intention and could fully mediate between perceived ease of use on online repurchase intention. The implication is that marketplace sites need to improve e-satisfaction through e-service quality, which is continuously improved and provides easy-to-understand features for consumers; thus, it can encourage the desire to repurchase products/services on the marketplace site.  Keywords:E-Service Quality, Perceived Ease of Use, E-Satisfaction, Online Repurchase Intention, Marketplace